EFFECT OF Piper tuberculatum EXTRACT ON ADULT Schistosoma mansoni: in vitro AND in vivo TESTS - Simões, Luciana Franceschi (2015)
Schistosomiasis is a severely neglected disease with a wide geographical distribution. It affectsapproximately 210 million people in the world and at least 800 million people live in risk areas.The search for new drugs to treat this parasitosis is significant due to the appearance of strains of theworm that are resistant to the currently available drugs. The retrieval of compounds extracted fromplants that act on these parasites has increased scientific investigation of this subject. The presentstudy demonstrates, in vitro and in vivo, the action of crude extract of Piper tuberculatum on adultSchistosoma mansoni. The extract was shown to be quite effective in the in vitro tests, causing softtissue alterations and acting on the reproductive system of females and the mortality of the worms,with a greater effect on males. The in vivo experiment was performed with infected Mus musculusand a decrease in the number of eggs in the first and second oogram stages was found, suggestingaction on oviposition.